Aplikasi Penjualan Pakaian Dan Aksesoris Menggunakan Visual Basic (Studi Kasus : Toko Chya Shop) - Lusia Goo; Kristianus Jago Tute; Benediktus Yoseph Bhae (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
The problem in this research is that the information system on the sale of clothing and accessories that is being used to manage sales data and inventory is still conversion, namely using a bookkeeping system, where operational activities do not utilize the existing computer. So the purpose of this research is to design and create an application for selling clothes and accessories using visual basic at the Chya Shop Shop. The method used in this study is a descriptive qualitative method with data collection techniques in the form of observation, interviews and documentation. System development using the Rapid Application Development (RAD) method and testing using black box testing. The result of the system created is to be able to make clothing and accessories sales applications well and can be implemented. The conclusion is that the application of clothing and accessories sales can provide information about stock data of goods, sales data and presentation of reports based on a certain period in order to make it easier for owners to manage inventory. Keywords: Sales Application, RAD, Black Box Testing.